OPTIMIZING THE ROLE OF ISLAMIC EDUCATION AS AN EFFORT AGAINSTS HOAX NEWS IN GLOBALIZATION ERA - Muhammad Choirunniam; Ashif Az Zafi (Al Ulya: Jurnal Pendidikan Islam, 2021)
Fake news or hoaxes are things that must be anticipated along with the development of sophisticated technology in the current era of globalization. Like a smartphone which contains all the information that can be entered at any time without any filtering, it must be anticipated whether the news or information contains truth or lies. If it is not properly anticipated, there will be continuous problems, which can even lead to division in this country. So this research aims through Islamic education as a hope that can be optimized by instilling noble behavior values, namely honesty from an early age, to be able to break the chain of dissemination and prevent fake news in this era of globalization. The method used by researchers here is descriptive qualitative. Islamic education in its implication is physical and spiritual guidance to create a personal Islamic character. So it is not easy to slander other people or create a lie that can harm other people.